2019
DOI: 10.5430/jct.v8n4p30
|View full text |Cite
|
Sign up to set email alerts
|

Experiential and Real-World Learning for Teachers in the Billion Oyster Project and Curriculum and Community Enterprise (BOP-CCERS) for the Restoration of New York Harbor with New York City Public Schools Program

Abstract: The Billion Oyster Project and Curriculum and Community Enterprise for the Restoration of New York Harbor withNew York City Public Schools (BOP-CCERS) seeks to integrate harbor restoration activities with science teachers inorder to provide their students with experiential learning through environmental impact in New York City with thevision that public school students in New York City can benefit from environmental science and experiential learningwork through authentic research, data collection, and experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Teachers in the BOP-CCERS program reported that they are better prepared to teach scientific research, oyster biology and ecological restoration. Students who engage in real-world science learning activities are more likely to see the relevance of science and see themselves working toward a STEM career pathway (Birney et al, 2019).…”
Section: Figure 1 Stem Career Interestmentioning
confidence: 99%
“…Teachers in the BOP-CCERS program reported that they are better prepared to teach scientific research, oyster biology and ecological restoration. Students who engage in real-world science learning activities are more likely to see the relevance of science and see themselves working toward a STEM career pathway (Birney et al, 2019).…”
Section: Figure 1 Stem Career Interestmentioning
confidence: 99%